Public Relations as Viewed by Employees of Polish Welfare Institutions - Michał Szyszka (Communication Today, 2025)
The article discusses the issue of Public Relations (PR) and its use in Polish social welfare institutions. At present, we can observe that Polish social welfare industry faces serious problems related to its public image. This is due to: insufficient experience in Public Relations, lack of systemic actions towards improving the prestige of social work as well as creating the image of social welfare. The text offers a comparison of beliefs and opinions expressed by the employees of the Polish public welfare institutions; these opinions and views are related to PR and communication practices applied by their organisations. The opinions were collected through a nationwide survey. The results include very interesting findings: for instance, they confirm the thesis about the lack of regular and constructive communication and image-related activities carried out on the institutional level and low evaluation of their effectiveness. The conclusions, however, also point out that the respondents revealed that they are highly aware of the importance of PR operations as well as of the correlations between these operations and how their institutions are seen by the general public and by the media. This may be interpreted as prospects and chances for further application of communication tools in social policy institutions.